The planning, development and management of tourism: The case of Dangjia, an ancient village in China. (October 2016) - Guo, Zhanfeng; Sun, Li
Abstract: "Ancient villages" are rural settlements in China that achieve this classification because of their historic, cultural and architectural values. Nonetheless, while they have long histories and are considered as tourism assets they may also face social, economic, environmental and political problems. This article analyses these issues using a qualitative and quantitative analysis derived from research at Dangjia Ancient Village, Shaanxi, China. It identifies changing patterns in demand and shifts in the modes of meeting those demands – from modes that are individually based to those that are dependent on local government interventions. Much of this change is due to deficiencies in local social and financial capital. Suggestions are made regarding ways to improve the sustainability of rural tourism, which have a wider application on a national and international scale. Highlights: 'Ancient Villages' in China have abundant material and social culture for tourism. Tourism management has shifted from village-based to local government intervention. Few villagers succeed in generating direct private incomes from tourism. Without villagers' participation, deserted ancient courtyard houses reduce the value of the site. Suggestions and lessons are derived to improve the sustainability of rural tourism.